Assessment of nitrogen nutrient sources in aquatic environment of Tuyen Lam sub-catchment based on it’s stable isotopes ratio (δ¹⁵N-NO3) combined with geochemical parameters - Nguyen Thi Huong, Lan; Nguyen Minh, Dao; Phan Quang, Trung; Vo Thi Mong, Tham; Le Xuan, Thang; Phan Son, Hai; Nguyen Van, Phuc (Nuclear Science and Technology, 2020)
Overloading and erosion of pollutants, especially nitrogen (nitrate and ammonium) nutrient, in catchment of multiple land use put pressure on the quality of surface water. Excess of nitrogen nutrient in the aquatic environment causes eutrophication leading to adverse effects to the habitat and ultimately it could affect the human health through the food chain. The aim of this study is to assess the sources of nitrogen nutrient that could affect the quality of surface water at a subcatchment of Tuyen Lam reservoir in Lam Dong province by the use of water’s physico-chemical parameters combined with stable isotope ratio of nitrogen in nitrate (δ15N-NO3) dissolved in the water. It was revealed that nitrogen nutrient in water from springs in the study area came from at least three sources: decomposition of soil organic matters, inorganic fertilizers and water waste from residential areas. In points of annual crop farming and close to residential the contribution of inorganic fertilizers to the total concentration of nitrate was estimated, based on the δ15N-NO3 values, to be as high as more than 60% and the contribution of water waste was around 35-40%. This is the first time isotopic signature of nitrogen-15 in nitrate (δ15N-NO3) was applied as a tool to assess and identify sources of the nutrient in aquatic environment. Results of this study, although it was initial but it would be useful for the local environmental managers in developing suitable strategies to control over nitrogennutrient releases in order to keep the aesthetic appeal of Tuyen Lam Reservoir.